INCREASING CHILDREN'S CREATIVITY AND SKILLS THROUGH HANDICRAFTS FROM USED BOTTLE WASTE - Devi Lisnawati; Maha Putra; Muhamad Virgi Pratama; Rudi Septian (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
Creativity is a person's ability to produce new ideas that are original and useful, and able to overcome problems in unconventional or new ways. Skills or skills are special abilities or skills that a person has in doing something well and skillfully. Usually, this skill can be learned and improved through practice and experience. Used bottle crafts are the art or skill of turning used bottles into useful or decorative items. This can include techniques such as cutting, painting, decorating, and combining with other materials to create unique and useful new products. This craft can not only reduce plastic waste, but also create items with high aesthetic value. The benefits of increasing children's creativity are teaching children to collaborate with others, learn from their ideas, and communicate their ideas clearly. The aim of turning used bottles into useful items can help reduce the amount of plastic in the community. The research subjects were children. Almost 100% of participants answered that they wanted to participate again in making crafts from bottles. This was also reflected in their goals and results, and their goals had increased when they started making crafts after teaching skill theory. These children's activities show how many children -children who use waste bottles that are often thrown away to make good handicrafts that are no less good than other crafts and might be worth selling.